2019
DOI: 10.1111/cid.12825
|View full text |Cite
|
Sign up to set email alerts
|

Single crown restorations supported by 6‐mm implants in the resorbed posterior mandible: A five‐year prospective case series

Abstract: Purpose To assess clinical performance of single restorations supported by 6‐mm long implants in the posterior mandible after 5 years in function. Materials and Methods Twenty‐one consecutive patients with the absence of premolars or molars in the posterior mandible and an estimated bone volume of at least 6 mm in width and an estimated height of 8 mm between the top of the ridge and alveolar nerve were included. Each patient received one or more 6‐mm implants. Custom‐made titanium abutments with cemented zirc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…Twenty of the included studies were RCTs (Table 2; Table ) comparing directly veneered zirconia customized and stock zirconia abutments with cemented ceramic SCs (Wittneben et al, 2020), esthetic outcomes for screw‐retained SCs with or without using provisional crowns for tissue conditioning (Furze et al, 2019), metal‐ceramic and resin‐matrix ceramic SCs (Agustín‐Panadero et al, 2020), monolithic zirconia and porcelain‐fused‐to‐metal (PFM) implant‐supported SCs (Mühlemann et al, 2020), cemented and screw‐retained SCs on customized zirconia abutments (Heierle et al, 2019), 11 mm implants used in combination with sinus floor elevation and 6mm implants without bone augmentation (Guljé et al, 2019b), screw‐retained monolithic zirconia and cemented PFM SCs (Weigl, Saarepera, et al, 2019), submucosal veneered zirconia abutments and non‐veneered zirconia abutments (Laass et al, 2019), immediate, non‐detached glass‐ceramic individualized abutments and dis‐/reconnections (Erhan Çömlekoğlu et al, 2018), monolithic zirconia SCs and short‐span FDPs (Cheng et al, 2019), cemented and screw‐retained zirconia‐based implant‐supported SCs (Kraus et al, 2019), tooth‐ and implant‐supported veneered zirconia single SCs (Cantner et al, 2019), cemented and screw‐retained CAD/CAM zirconia abutments for esthetically located implant‐supported SCs (Amorfini et al, 2018), digital and analog procedures for manufacturing of implant‐supported SCs (Mangano & Veronesi, 2018), customized zirconia and titanium abutments (Bösch et al, 2018), immediately loaded one‐ and two‐piece implants (Bomicke et al, 2017), two‐piece and one‐piece zirconia abutments (Paolantoni et al, 2016), bonding of a RMC restorative material to zirconia stock abutments and zirconia customized abutments (Schepke et al, 2016), zirconia and titanium abutments (Zembic et al, 2013), and zirconia and metal‐ceramic implant‐supported SCs (Hosseini et al, 2011) (Table ). The remaining 29 studies were prospective cohort studies (Andersson et al, 1998; Cantner et al, 2019; Canullo, 2007; Cheng et al, 2019; Cooper et al, 2016; Fenner et al, 2016; Gierthmuehlen et al, 2020; Guarnieri et al, 2015; Guljé et al, 2019a; Guncu et al, 2016; Henriksson & Jemt, 2003; Hosseini et al, 2011; Hosseini et al, 2013; Joda et al, 2017; Kolgeci et a...…”
Section: Resultsmentioning
confidence: 99%
“…Twenty of the included studies were RCTs (Table 2; Table ) comparing directly veneered zirconia customized and stock zirconia abutments with cemented ceramic SCs (Wittneben et al, 2020), esthetic outcomes for screw‐retained SCs with or without using provisional crowns for tissue conditioning (Furze et al, 2019), metal‐ceramic and resin‐matrix ceramic SCs (Agustín‐Panadero et al, 2020), monolithic zirconia and porcelain‐fused‐to‐metal (PFM) implant‐supported SCs (Mühlemann et al, 2020), cemented and screw‐retained SCs on customized zirconia abutments (Heierle et al, 2019), 11 mm implants used in combination with sinus floor elevation and 6mm implants without bone augmentation (Guljé et al, 2019b), screw‐retained monolithic zirconia and cemented PFM SCs (Weigl, Saarepera, et al, 2019), submucosal veneered zirconia abutments and non‐veneered zirconia abutments (Laass et al, 2019), immediate, non‐detached glass‐ceramic individualized abutments and dis‐/reconnections (Erhan Çömlekoğlu et al, 2018), monolithic zirconia SCs and short‐span FDPs (Cheng et al, 2019), cemented and screw‐retained zirconia‐based implant‐supported SCs (Kraus et al, 2019), tooth‐ and implant‐supported veneered zirconia single SCs (Cantner et al, 2019), cemented and screw‐retained CAD/CAM zirconia abutments for esthetically located implant‐supported SCs (Amorfini et al, 2018), digital and analog procedures for manufacturing of implant‐supported SCs (Mangano & Veronesi, 2018), customized zirconia and titanium abutments (Bösch et al, 2018), immediately loaded one‐ and two‐piece implants (Bomicke et al, 2017), two‐piece and one‐piece zirconia abutments (Paolantoni et al, 2016), bonding of a RMC restorative material to zirconia stock abutments and zirconia customized abutments (Schepke et al, 2016), zirconia and titanium abutments (Zembic et al, 2013), and zirconia and metal‐ceramic implant‐supported SCs (Hosseini et al, 2011) (Table ). The remaining 29 studies were prospective cohort studies (Andersson et al, 1998; Cantner et al, 2019; Canullo, 2007; Cheng et al, 2019; Cooper et al, 2016; Fenner et al, 2016; Gierthmuehlen et al, 2020; Guarnieri et al, 2015; Guljé et al, 2019a; Guncu et al, 2016; Henriksson & Jemt, 2003; Hosseini et al, 2011; Hosseini et al, 2013; Joda et al, 2017; Kolgeci et a...…”
Section: Resultsmentioning
confidence: 99%
“…In previous clinical studies, short-implant (≤6 mm) survival rates were similar to those of standard implants (>6 mm) (Pieri et al, 2017;Abduljabbar et al, 2018;Thoma et al, 2018;Guljé et al, 2019aGuljé et al, , 2019b. However, one study found that over 5 years, the survival rate of 6-mm implants was significantly lower than that of 10-mm implants (86.7% vs. 96.7%) (Rossi et al, 2016).…”
Section: Introductionmentioning
confidence: 54%
“…Several studies have suggested that, in the posterior region, splinted restoration should be considered if short implants are used (ten Bruggenkate et al, 1998;Misch et al, 2005;Renouard & Nisand, 2006;Draenert et al, 2012;Vazouras et al, 2020). However, single crowns supported by 6-mm short implants have been used in several studies with predictable clinical outcomes (Rossi et al, 2015;Thoma et al, 2018;Guljé et al, 2019aGuljé et al, , 2019b. In those studies, short implants had survival rates and MBL similar to those of longer implants.…”
Section: Implant Survival and Successmentioning
confidence: 99%
“…In this study, concerning implant survival outcomes and marginal bone levels changes over time, no statistical differences among 8‐, 6‐ (short), and 5‐mm length (ultra‐short) implants, supporting single crowns in the posterior maxilla and mandible, were demonstrated 5 years after loading. In the past decades, several authors supported the idea that <8 mm in length implants could be considered a valid option of treatment not only in case of splinted reconstructions but also for single‐unit restorations 30,46–48 . However, considering that most of the studies were conducted with a short (1–3 years) follow‐ups, other authors 4 recommended that these results should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%